Comparison of CKD-EPI Cystatin C and Creatinine Glomerular Filtration Rate Estimation Equations in Asian Indians - Boon Wee Teo; Charumathi Sabanayagam; Jiemin Liao; Qi Chun Toh; Sharon Saw; Tien Yin Wong; Sunil Sethi (International Journal of Nephrology)
Background. Chronic kidney disease (CKD) is identified in the general population using estimated glomerular filtration rates (eGFR) calculated from a serum creatinine-based equation, the chronic kidney disease-epidemiology collaboration (CKD-EPI) equation. Using serum cystatin C in combination may improve eGFR accuracy. We evaluated the new CKD-EPI equations incorporating cystatin C in a population of Asian Indians in classifying CKD across body mass index, diabetes, and hypertension status. Methods. We retrieved standardized serum creatinine and serum cystatin C data from a cohort of 2877 Asian Indians aged 40–80 years from the Singapore Indian Eye Study and calculated eGFR (in mL/min/1.73 m2) with the new CKD-EPI equations and serum creatinine only equation. Results. The creatinine only equation mean eGFR (88 ± 17) was similar to using spline Log cystatin C (88 ± 22). The lowest mean eGFR (81 ± 21) was obtained with the spline Log cystatin C—age, sex, and weight equation. The creatinine only equation had the fewest participants (7.1%) with eGFR <60 and spline Log cystatin C—age, sex, and weight equation had the most (16.1%). Conclusions. Using serum cystatin C resulted in widely varying eGFR which significantly affected the classification of chronic kidney disease.